Synthesis of 2-Amino Dihydropyrimidines,Their Thiocarbamide Derivatives and Study of Their Antimicrobial Activity - Heda, P.B.; Ghiya, B.J. (Asian Journal of Chemistry, 2010)
Various substituted acetophenones (I) were prepared by Fries migration of substituted phenyl acetates. (I) on Claisen-Schmidt condensation with substituted aromatic aldehydes in presence of 40% NaOH gave different substituted chalcones (II). (II) on cyclocondensation with guanidine carbonate in ethylene glycol gave 2-amino-5,6-dihydro pyrimidines (III). (III) on reaction with phenyl isothiocyanate in benzene gave respective thiocarbamide derivatives (IV). Structures of compounds (III) and (IV) were confirmed on the basis of elemental analysis, chemical properties and IR, NMR and mass spectra. Antimicrobial activities of some of the synthesised compounds was also studied.